Islamic Social Financial Instruments and Sustainable Community Development: Evidence Synthesis on Community Resilience - Abdallah Mambo Dallu (Journal of Islamic Monetary Economics and Finance, 2026)
This study investigates how Islamic Social Finance (ISF)—through zakat, waqf, and sadaqah—supports sustainable community development by strengthening economic, social, institutional, psychological, and environmental resilience. Using a PRISMA-guided systematic literature review and bibliometric analysis of 93 studies published between 2010 and 2025, the paper synthesizes fragmented scholarship to identify the mechanisms through which ISF enhances resilience. Findings show that zakat provides short-term stabilization and crisis relief, waqf enables long-term asset creation and public-goods provision, and sadaqah delivers flexible emergency support. Integrated ZISWAF models, particularly those inspired by Ascarya, emerge as the most effective structure for maximizing development outcomes when supported by strong governance, institutional coordination, and digital innovation. The study contributes (i) a consolidated evidence highlighting thematic fragmentation in ISF research; (ii) an integrated conceptual map linking ISF to resilience theory and the SDGs; and (iii) a multidimensional framework explaining how ISF instruments jointly foster community resilience. Policy recommendations include strengthening governance and regulatory coherence, accelerating digital transformation, adopting integrated ZISWAF delivery models, and expanding ISF applications in environmental sustainability and climate resilience.